2017
DOI: 10.21839/jaar.2017.v2i6.122
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the Mediterranean Diet on Chronic Diseases: Cardiovascular Diseases, Oxidative Stress, Dyslipidemia, Diabetes Mellitus, Blood Pressure, Cancer, Neurodegenerative Disease and Obesity

Abstract: Poor dietary habits lead to the emergence of chronic diseases such as coronary heart disease, stroke, hypertension, diabetes mellitus, dyslipidemia, cancer, dementia, obesity and oxidative stress involved through the aggression of cells by free radicals, Knowing that these diseases cause a global burden both individually and economically, Several studies focus on the relationship between diet and chronic disease. Studies suggest that the Mediterranean diet, (MD) traditional eating habits and lifestyle specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 121 publications
(133 reference statements)
0
1
0
Order By: Relevance
“…2,3 Dietary factors are important for maintaining optimal weight and good health, and poor dietary habits lead to the emergence of chronic diseases such as cancer, coronary heart disease, stroke, hypertension, diabetes mellitus, dyslipidemia, dementia, obesity and oxidative stress. 4 In literature it is indicated that major chronic diseases are closely related to dietary factors, and it is the case in South Korea. According to the records in 2016, more than one in three adults are obese.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Dietary factors are important for maintaining optimal weight and good health, and poor dietary habits lead to the emergence of chronic diseases such as cancer, coronary heart disease, stroke, hypertension, diabetes mellitus, dyslipidemia, dementia, obesity and oxidative stress. 4 In literature it is indicated that major chronic diseases are closely related to dietary factors, and it is the case in South Korea. According to the records in 2016, more than one in three adults are obese.…”
Section: Introductionmentioning
confidence: 99%